Existence Deep Local Wisdom Policy Development Tourism in Tenganan Village Gringsingan Karangasem Regency, Bali Province - I Wayan Surpa; I Gusti Bagus Wirya Agung (International Journal of Educational Research Excellence (IJERE), 2023)
Indonesia as a plural country with a variety of cultural diversity and customs that characterize the local wisdom of each region in Indonesia. This local wisdom is still very thick and maintained by the community so as to create its own uniqueness for the Indonesian state. This local wisdom, if packaged properly, has the potential to create local charm or local branding that can be used as one of the tourist attractions that can help the local economy. Thus, it is necessary to develop tourism based on local wisdom. Tenganan Village as one of the tourist villages in Bali has characteristics as a cultural tourism destination that highlights the ancient Balinese culture. This study aims to determine how local wisdom exists in tourism development policies in Tenganan Pegringsingan Village, Karangasem Regency. This research uses qualitative methods with a case study approach to be able to describe, explain, and analyze existing problems. The informants in this study include Anna Christiana as Head of Tourism Destination and Marketing Division, I Ketut Sudiastika as Perbekel of Tenganan Pegringsingan Village, I Putu Wiadnyana as Manager of Tenganan Pegringsingan Tourism Village and Putu Yudiana ST as Bendesa Adat of Tenganan Village. The results obtained show that Tenganan Village still maintains its local wisdom as a tourism attraction amid the onslaught of growing tourism trends. With the tourism development policy, Tengenan Pegringsingan Village can manage its tourism independently.